Fully replicable and automated retention measurement setup for characterization of bio-adhesion - Lukas Vaut (HardwareX, 2019)
The retention model by Rao and Buri is often used to characterize microparticles and other drug delivery systems for their bio-adhesive properties. Currently, these experiments are performed on customized setups, reducing reproducibility of results obtained in different labs. As a solution, we propose a fully replicable retention model, which can be constructed by parts mostly made by 3D printing and laser cutting as well as a limited amount of other easy to source and commercially available parts. In addition of being fully replicable, the setup features integration of a climate-controlled chamber, a peristaltic pump and an autosampler, thereby enabling fully automated but customized control of the experiments. Using the presented retention model setup and an automated experimental sequence, the setup has been proven capable of investigating mucoadhesion of differently shaped particles to porcine intestinal tissue. Keywords: Open source hardware, Open labware, Retention model, Ex vivo flow model, Flow-through method, Bioadhesion, Mucoadhesion